Phospholipases AtPLDζ1 and AtPLDζ2 function differently in hypoxia. Issue 1 (7th November 2017) - Lindberg, Sylvia; Premkumar, Albert; Rasmussen, Ulla; Schulz, Alexander; Lager, Ida
Abstract : Besides hydrolyzing different membrane phospholipids, plant phospholipases D and molecular species of their byproducts phosphatidic acids (PLDs/PAs) are involved in diverse cellular events such as membrane‐cytoskeleton dynamics, hormone regulation and biotic and/or abiotic stress responses at cellular or subcellular levels. Among the 12 Arabidopsis PLD genes, PLDζ1 and PLDζ2 uniquely possess Ca 2+ ‐independent phox (PX) and pleckstrin (PH) homology domains. Here, we report that mutants deficient in these PLDs, pldζ1 and pldζ2, show differential sensitivities to hypoxia stimulus. In the present study, we used protoplasts of wild type and mutants and compared the hypoxia‐induced changes in the levels of three major signaling mediators such as cytoplasmic free calcium [Ca 2+ cyt. ], hydrogen peroxide (H2 O2 ) and PA. The concentrations of cytosolic Ca 2+ and H2 O2 were determined by fluorescence microscopy and the fluorescent dyes Fura 2‐AM and CM‐H2 DCFDA, specific for calcium and H2 O2, respectively, while PA production was analyzed by an enzymatic method. The study reveals that AtPLDζ1 is involved in reactive oxygen species (ROS) signaling, whereas AtPLDζ2 is involved in cytosolic Ca 2+ signaling pathways during hypoxic stress. Hypoxia induces an elevation of PA level both in Wt and pldζ1, while the PA level is unchanged in pldζ2 . Thus, it is likely that AtPLDζ2 is involved in PA production by a calcium signaling pathway, while AtPLDζ1 is more important in ROS signaling.